The Paleopathology of specific infectious diseases from Southeastern Hungary: a brief overview - Pálfi, György; Molnár, Erika (Acta Biologica Szegediensis, 2009)
The purpose of this study is to review the evidence for the presence of specific infectious diseases in past Hungarian populations. As for treponemal diseases, only few paleopathological cases had been published until relatively recently. New discoveries from the medieval Szeged furnished evidences for the Pre-Columbian occurrence of the disease in this area. Among mycobacterial infections, paleopathological analyses of thousands of skeletons provided a relatively high number of observations of ’classical’ skeletal tuberculosis (TB) cases, and some cases of leprosy until the end of the 1990’s. The use of DNA assays and the study of early stage traces of mycobacterial skeletal infections highly increased the number of observations during the last ten years. Unfortunately, these results present several biases of the classical osteoarcheological studies, such as the differentiation between the taphonomic and paleodemographic conditions of the series. The evolution of the paleopathological diagnostical methods necessitates the complete re-evaluation of the previously studied materials in order that we can obtain a more realistic paleoepidemiological picture of these diseases.